MINORITY-LANGUAGE PUBLISHING IN THE REPUBLIC OF ESTONIA DURING THE PRE-WAR YEARS (1918–1940) AND NOWADAYS - Möldre, Aile (Knygotyra, 2016)
The article includes an overview about the publishing and book production in minority languages in Estonia during the periods of the independent Republic of Estonia – in 1918–1940 since 1991 with Estonian reestablished as the official language. The treatment is based on the statistical data calculated on the basis of the Estonian National Bibliography database and on the thematic analysis of numerous research works.Russians and Germans were the largest minority groups in Estonia in 1918–1940. They were able to establish and operate publishing houses specializing correspondingly in Russian or German-language production. The German-language book title output was higher than in Russian, which was partly due to the role of German in science at that time. The smaller ethnic groups of Jews and Swedes mainly published periodicals.Only one historical minority – the Russian – survived through World War II and post-war period, making the Russian-language publishing the only enduring minority-language publishing venture in the present-day Estonia.
Keywords: minority; publishing; book production; publishing houses; Estonia